2019
DOI: 10.1038/s41416-019-0449-y
|View full text |Cite
|
Sign up to set email alerts
|

Intratumor heterogeneity of PD-L1 expression in head and neck squamous cell carcinoma

Abstract: Intratumor heterogeneity may contribute to the ambiguous clinical results on PD-L1 status as a predictor for immunotherapy response in patients with HNSCC. This decreases the utility of PD-L1 expression from single tumour biopsies as a predictive biomarker. In this prospective study, intratumor heterogeneity of PD-L1 expression in HNSCC was investigated with both Tumour Proportion Score (TPS) and Combined Positive Score (CPS). Thirty-three whole surgical specimens from 28 patients with HNSCC were included. PD-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
74
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(89 citation statements)
references
References 18 publications
2
74
3
Order By: Relevance
“…The comparability between the results is limited [14,15]. Due to the reported heterogeneity of PD-L1 expression in other head and neck malignancies [23], we also see the use of tissue microarray (TMA) slides for the first assessment of PD-L1 expression somewhat critical. Our result of high PD-L1 expression in AC, NOS is in line with data from Mukaigawa et al who reported PD-L1 expression (1% cutoff, clone E1L3N) in 36% of AC, NOS but only in rare cases of AdCC (2%), MEC (9%), and ACC (0%) [22].…”
Section: Discussionmentioning
confidence: 99%
“…The comparability between the results is limited [14,15]. Due to the reported heterogeneity of PD-L1 expression in other head and neck malignancies [23], we also see the use of tissue microarray (TMA) slides for the first assessment of PD-L1 expression somewhat critical. Our result of high PD-L1 expression in AC, NOS is in line with data from Mukaigawa et al who reported PD-L1 expression (1% cutoff, clone E1L3N) in 36% of AC, NOS but only in rare cases of AdCC (2%), MEC (9%), and ACC (0%) [22].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that PD-L1 CAR haNK monotherapy may be most effective in patients harboring PD-L1+ tumors with evidence of genomic alterations or expression defects predicted to lead to insensitivity to T cell detection or elimination. Greater than 80% of patients with HNSCC have a combined positive score of >1 indicative of PD-L1 positivity(28), but significant heterogeneity of PD-L1 expression exists within individual tumors(29). PD-L1-dependent and independent mechanisms of killing by PD-L1 CAR haNKs are likely to be required for maximum treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The caveat of using CPS at the 1% cutoff to select HNSCC patients for PD-1 ICB is that intratumor heterogeineity should be considered. Rasmussen et al have prospectively investigated the intratumor heterogeneity in PD-L1 expression in HNSCC in 28 patients with a total of 33 whole surgical specimens (98). With 1% cut off, 52% of the six random core biopsies from each surgical specimen was concordant with CPS.…”
Section: Prediction Of Response To Anti-pd-1 Immunotherapy In Hnsccmentioning
confidence: 99%
“…With 1% cut off, 52% of the six random core biopsies from each surgical specimen was concordant with CPS. Defining a tumor as positive if just a single-one of the core biopsies was positive using CPS at 1% cut-off, the negative predictive value of a single negative core biopsy was 0% (98).…”
Section: Prediction Of Response To Anti-pd-1 Immunotherapy In Hnsccmentioning
confidence: 99%